Análisis bibliométrico sobre trabajo y salud laboral en trabajadores informales, 2010-2016. - Johana Puentes-León, Katherin; Rincón-Bayona, Lyda Yolima; Puentes-Suárez, Alexandra (Revista Facultad Nacional de Salud Pública)
Objective: To analyze the scientific production published between 2010 and 2016 in the databases of free access and restricted, on labor and occupational health in informal workers. Methodology: this paper presents a review of the scientific literature on work and health in informal workers, published in the free databases and restricted access. This descriptive study is developed from bibliometric indicators: content, affiliation of the authors, methodology and productivity. Results: It took 71 units of analysis that met the inclusion criteria. In the study, the 32 % of the articles develop topics related to the working conditions and health,the economy activity various in different sectors and categorized as informal activities, where street vendors and waste pickers. Analyzed studies identify different risks and its impact on the associated health working conditions, in terms of labor characteristics lack of affiliation to the social security system, long working hours and violation of the rights stands. The main reasons for admission to informality include the inability to be employed in the formal sector. Mostly the authors contributing to this issue are transient. Colombia provides 45 % of the total production on this topic. It highlighted in 2013 as the largest publication. Conclusions: It is necessary to develop studies on health and safety education, or appropriation of labor rights and creating guides.